The pure models of the political regime: English parliamentarism and the North American presidential regime - Ruiz Hidalgo, Rafael Manuel (2021)
The Pure Models of Political Regime: The English parliamentary government and the American Presidential System  These two models are pure regimes, countries called classical democracy devised their own system of government whose origin stems in most types of regimes to becoming a State, the same as is dew from the Historical Constitution peculiar case as the System English, which although lacking a written Constitution, however, the constitutional system is flexible and can adapt to the changing times and this permeable to changes and technological advances of society constitutional system. But the American model has its own nuances the “Pure American Presidential Regime”, establishing the origin of this system of the Constitution of 1787, with a feature of the system where there is a real division of powers: executive, legislative and Judicial. A system of checks and balances characteristic of this democratic system, considered-the constitutional doctrine as a country of democracy in classical Maurice Duverger words.